The Oxford Handbook of Cuneiform Culture 2012
DOI: 10.1093/oxfordhb/9780199557301.013.0033
|View full text |Cite
|
Sign up to set email alerts
|

Changing Images of Kingship in Sumerian Literature

Abstract: This article examines changes in the images of kingship in Sumerian literature, particularly in the hymns, myths, and narratives of the late third and early second millennia bc. It investigates whether ancient Mesopotamian kings were able to influence and model intellectual activity in order to maintain and support their political rule. The analysis reveals that royal hymns and other literary texts, such as the Sumerian Gilgameš tales and the narratives surrounding Enmerkar and Lugalbanda, the legendary kings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…They collected libraries and archives to document official transactions and to develop references for their personal uses (Robson, 2011), engaged in historical synthesis of prior knowledge of professions (De Breuker, 2011), developed literary letter writing (Vulliet, 2011), and composed dirges, laments, and prayers for the kings (Löhnert, 2011;Tanret, 2011). In their poetic and other literary genres they developed representations of the self, including some degrees of awareness of agency, freedom, death, and history, (Foster, 2011;Van Koppen, 2011), even while they kept thematic focus on the praise and projection of royal power and ideal kingship (Brisch, 2011;Waerzeggers, 2011).…”
Section: Cuneiform Writing and Scribal Culturementioning
confidence: 99%
“…They collected libraries and archives to document official transactions and to develop references for their personal uses (Robson, 2011), engaged in historical synthesis of prior knowledge of professions (De Breuker, 2011), developed literary letter writing (Vulliet, 2011), and composed dirges, laments, and prayers for the kings (Löhnert, 2011;Tanret, 2011). In their poetic and other literary genres they developed representations of the self, including some degrees of awareness of agency, freedom, death, and history, (Foster, 2011;Van Koppen, 2011), even while they kept thematic focus on the praise and projection of royal power and ideal kingship (Brisch, 2011;Waerzeggers, 2011).…”
Section: Cuneiform Writing and Scribal Culturementioning
confidence: 99%
“…Naram‐Sin was the grandson of Sargon, the founder of the Old Akkadian dynasty. Naram‐Sin’s reign, during which he faced several rebellions against his centralized rule, initiated the beginning of the end of the Old Akkadian state, and in the native Mesopotamian cultural memory he acquired a reputation of being an “unsuccessful king” (Brisch 2011: 715–7), though it is unlikely that this was related to his deification being perceived as sacrilegious (see below).…”
Section: The First Divine King: Naram‐sin Of Akkadmentioning
confidence: 99%
“…The latter is especially interesting as it has been suggested that Amar‐Suen was subject of a damnatio memoriae , initiated by his son and successor Shu‐Sin (Sallaberger 1999: 167). Although Amar‐Suen acquired the reputation of an “unlucky ruler” in later periods (Brisch 2011: 715–7), it is possible that Ibbi‐Sin tried to counter‐act this negative legacy. However, Ibbi‐Sin’s attempts may have been unsuccessful; the Correspondence of the Kings of Ur (Michalowski 2011) depicts him as a weak ruler who lost control of his empire and was taken captive by his enemies, thereby ending the Third Dynasty of Ur.…”
Section: The Apex Of Divine Kingship: the Third Dynasty Of Urmentioning
confidence: 99%